Effect of U-Turn Use at Signalized Intersections: A Case of Simpang Frenky, Batam - Kelvin Saputra Mulyadi; Yusra Aulia Sari (Fakultas Teknik Sipil dan Perencanaan, 2023)
U-Turn is one of the infrastructures to change direction on the highway. U-Turns also increase access to mobility in the economic growth of the country. U-Turns are allowed at intersections in signalized or unsignalized research if they do not cause potential accidents, of course, taking into account road width, volume, and vehicle speed. In a study conducted at the Simpang Frenky batam center signalized intersection, it was found that U-Turns caused a slowdown in vehicle speed.